Labeled NSAID hypersensitivity and the risk of opioid prescribing; an observational study - Abu Esba, Laila Carolina; Alhoraibi, Reham; Abu Al-Burak, Salem; Ardah, Husam I. (Frontiers in Allergy, 2025)
BackgroundNSAIDs are widely used for pain management but are second only to antibiotics in causing drug hypersensitivity reactions. Misclassification of these reactions often leads to unnecessary avoidance of the entire drug class, potentially resulting in increased opioid prescribing. This study aimed to assess the prevalence and characteristics of NSAID hypersensitivity, cross-reactivity patterns, and the association between NSAID hypersensitivity and opioid prescribing. The use of COX-2 selective inhibitors as a safe alternative was also explored.MethodsA retrospective cohort study was conducted at a tertiary care hospital, including patients with documented NSAID hypersensitivity between 2016 and 2023. Data on demographics, hypersensitivity reactions, NSAID cross-reactivity, and opioid prescriptions were collected. Patients with penicillin hypersensitivity were included for comparison. Logistic regression was used to analyze the association between NSAID hypersensitivity and opioid prescribing.ResultsAmong 319 patients with NSAID hypersensitivity, 30% (n = 96) were classified as true allergy, 12.5% (n = 40) as pseudo-allergy, and 57% (n = 183) were unclassified. Cross-reactivity between NSAIDs was observed in 13%, although 52% tolerated at least one other NSAID. Patients with NSAID hypersensitivity were 62% more likely to be prescribed opioids compared to those with penicillin hypersensitivity [adjusted OR 1.62 (95% CI: 1.40–1.88), p < 0.001]. Celecoxib was underutilized, prescribed to only 10% of hypersensitive patients.ConclusionNSAID hypersensitivity is associated with increased opioid prescribing due to class-wide avoidance. Despite concerns about cross-reactivity, many patients can tolerate alternative NSAIDs. Improved classification tools and clinical decision support systems are needed to guide prescribers.